Determinants of behavioral intention for interactive data extraction analysis (idea) among tax auditors in Sarawak state director office, irbm - Valin, Petrus (2020)
Effectiveness and efficiency have always been the priority of IRBM in delivering its services. This is including the introduction of various data analysis and enhancement tools such as Interactive Data Extraction Analysis (IDEA) to improve the existing work process. However, the number of IDEA utilization in current work process for IRBM tax auditor is still low if measured to the number of cases settled. This study attempts to identify the determinants of behavioural intention in using a new technology implemented at the workplace. This study adopted the Unified Theory of Acceptance and Use of Technology (UTAUT) with the addition of design characteristic in the independent variables. The data were collected from a sample of 56 tax auditors from six branches under Sarawak State Director Office which comprises of Kuching, Investigation Kuching, Sibu, Bintulu, Miri dan Investigation Miri branches by using a well-structured questionnaire. The Statistical Package for Social Science (SPSS) was utilized to perform the descriptive analysis, validity test, reliability test and regression analyse on the five hypothesized relationship. Findings revealed that only performance expectancy and design characteristics are significantly influenced behavioural intention to use IDEA auditing software. This revealed some point to be considered in encouraging the tax auditors to use the IDEA system such as make it as mandatory of IDEA application in tax audit tasks. The results highlighted some important facts to the authority (Inland Revenue Board of Malaysia) that any new system introduced will be considered if it is believed could improve performance and design characteristic in such a way with clear, understandable and easy application.